UPAYA REUNIFIKASI TAIWAN DITINJAU DARI PERKEMBANGAN KONFLIK SELAT TAIWAN PERIODE 1981-1991 - Prayogi, I Gede Candra (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2014)
ABSTRACT The civil war that occurred in China between the Communists and the Nationalists won by the Communists controlled mainland China as well. Nationalists were defeated, out of China and Taiwan as well as occupying three islands off the coast that Jinmen, Mazu, and Dazhen. Communist China tried to invade Taiwan and the third island away from the other coast to complement China. Conflict occurs when crossing the Communists attempted to occupy Taiwan, while Taiwan wants to be independent. Since going on the Taiwan Strait conflict, China and Taiwan are closed to each other each